Patient-centered intrathecal morphine dose response in major abdominal surgeries when augmented by innovative five-drug antiemetic prophylaxis - Williams, Brian A.; Hall, Daniel E.; Dalessandro, Chelsee; Garbelotti, Kelly E.; Ludden, John M. (Frontiers in Anesthesiology, 2025)
BackgroundFor abdominal surgery involving cephalad surgical trespass (such as sleeve gastrectomy and pancreatectomy), existing intrathecal morphine (ITM) recommendations of ≤150 μg may not achieve meaningful analgesia, potentially leading to side effects of intravenous opioids during or after surgery. This study aimed to present (i) an ITM dosing guideline to improve upon existing dosing guidelines (≤150 µg) and (ii) an analgesic duration predictor derived from the proposed vs. existing dosing guideline.MethodsWe used a mixed-method multi-hypothetical framework to demonstrate that five-drug antiemetic prophylaxis before spinal morphine administration may allow for ≥250 μg doses, which with further refinement may confer meaningful analgesia, downstream opioid sparing, and prevention of nausea/vomiting. A retrospective, case-matched quality improvement initiative was implemented, followed by multiple regression to (i) calculate successful spinal morphine dosing and (ii) predict analgesic duration in our Veteran patient population.ResultsAs opposed to the currently recommended dose of ≤150 μg, 250 μg was the start-point for spinal morphine dosing, with adjustments for gender, height, and age. The 250 μg dose (and incremental adjustments) was associated with a 16 h baseline analgesic duration, while the <200 μg dose was associated with only 8 h; the latter analgesic duration (i.e., ≤8 h) was adversely influenced by factors that did not affect the ≥250 μg dose analgesic duration.ConclusionWe achieved meaningful prophylaxis against nausea/vomiting with the five “keyword” drugs (all five drugs were used in 94% of our patients who received the ≥250 μg morphine dose). This seems to facilitate adherence to oral/enteral non-opioid analgesics after surgery, possibly contributing to analgesic duration. Conversely, avoidance of usual intraoperative (fentanyl, remifentanil, hydromorphone) and postoperative (hydromorphone, oxycodone, hydrocodone) opioids may have prolonged perceived analgesic duration (and avoided nausea) by preventing opioid-induced hyperalgesia and/or tolerance. We presume that the ≥250 μg morphine dose had sufficient “cephalad reach” for various procedures, including those where endoscopic cases were converted to open. This approach may prevent reflexive intraoperative administration of usual intravenous opioids. Five-drug antiemetic prophylaxis may allow for improved analgesic outcomes and systemic opioid reductions, via patient-based parameters of a spinal morphine dose start-point of at least 250 μg, as opposed to the currently recommended dose of ≤150 μg.